Efeito hall extraordinário em multicamadas granulares de SiO2/Co/CoO com exchange bias - Gomes, Matheus Gamino (2012)
Granular magnetic systems can be composed by magnetic particles or clusters with size of some nanometers. These magnetic nanoparticles present different magnetic order phases, as superparamagnetic, and they can be embedded in both, metallic or insulating matrix. These systems present several phenomena such as the giant magnetoresistance (GMR), extraordinary Hall effect (EHE), tunnel magnetoresistance (TMR) and Coulomb blockade. That phenomena use to disappear when a small termal fluctuation is high enough to reverse the magnetization of the clusters leading the lost the magnetic information in a very short time range. When it occurs, the particles are in superparamagnetic phase. In order to maintain the magnetic information at high values of temperature, or even to suppress the superparamagnetic limit, many works have tried to use an antiferromagnetic matrix, to induce the increase of the energy barrier among the two easy directions of magnetization by the exchange coupling in the grain(FM)/matrix(AFM) interfaces, with the purpose of stabilizing the particles magnetization. In this work, we have produced Co granular samples embedded in SiO2/CoO insulating/antifferomagnetic matrix through a sequential deposition by magnetron sputtering, in order to study the exchange bias of Co grains laterally surrounded by CoO.Were perfomed measurements of transmission eletronic microscopy (TEM), x-ray diffraction (XRD), measures low fields thermomagnetics (ZFC-FC), to obtain answers of the structural and magnétic charater of the samples. The Exchange Bias were investigated by extraordinary Hall effect, meauresments in differents temperature values in a cooling field (FC) of 5kOe. These non conventional measurements, are carried out with field cooling and the applied external field to perfomed the loop hysteresis both with perpendicular direction to the substrate. The effective anistropy, changes the magnitude up to three ordes of magnitude for different thicknesses of CoO in the limit T!0. On the other hand, the HEB linearily decreases, and goes to zero at a certain temperature. This temperature, is approximately, equal to that where the split of ZFC-FC curves occurs. This split is associated with the CoO blocking temperature, i.e. the ordering temperature of CoO. These results are reported from the finite size effect present in thin films. For the specific case of CoO, these effects lead to a nonzero net magnetization coming from uncompensed moments present on the surface that, in some cases, are responsible for the magnetic coupling governed by a local disorder and frustration, a spin-glass-like behavior. The extraodinary Hall effect and giant magnetoresistance were study of thin Fe-rich amorphous films and Fe-rich/Cu multilayers. Were investigated and compared the extraordinary Hall effect in these two types of samples and discussed it in terms of thickness and sample structure. The thicker films exhibited a strong in-plane magnetic anisotropy, and by decreasing film thickness both saturated Hall resistivity and Hall sensitivity increase. Electrical conductance increases and Hall resistivity decreases when the films are sandwiched with Cu.